Effect of riboflavin on rat bladder contractility and oxidant damage following ischemia/reperfusion - ERTAŞ, BÜŞRA (My University, 2023)
Ischemia/reperfusion (IR) encompasses the processes of organ function damage and oxidative injury depending on the successive blood flow obstruction and removal of the obstruction. Known as a vitamin, riboflavin (Rb) is known to be protective against tissue damage with its antioxidant and anti-inflammatory properties. The aim of this study is to investigate the effect of Rb treatment on bladder contraction dysfunction and tissue damage due to IR. The study was conducted with forty Sprague-Dawley rats. The abdominal aorta of anaesthetized rats was occluded to induce ischemia (60 min) and then allowed reperfusion (60 min). Rb (25 mg/kg), n-acetylcysteine NAC (100 mg/kg) or saline was administered orally 15 min before the IR model immediately. The bladder was assessed by biochemical and histological analysis, and the contractility of the I/R-related bladder was detected by organ bath. Compared to the control group, MDA, MPO and caspase-3 activities increased in the IR group, while GSH levels decreased. MDA, GSH and caspase-3 activities were reversed with Rb treatment, but there was no change in MPO level. Healing of IR-induced edema and oxidant damage with Rb and NAC treatment resulted in improvement of the thinning of the bladder wall. According to these results, it can be said that Rb therapy can regulate IR-induced bladder dysfunction by improving antioxidant properties and tissue damage.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); bladder; contractility response; Ischemia-reperfusion; riboflavin; Ischemia-reperfusion; riboflavin; bladder; contractility response